Association between intercellular adhesion molecule 1 (ICAM1) polymorphisms and diabetic foot susceptibility: A case–control study. Issue 11 (March 2020) - Cao, Xue-Xia; Yang, Jin-Kui; Wang, Li
Abstract : Abstract: The objective of the present study was to explore the association between intercellular adhesion molecule 1 ( ICAM1 ) polymorphisms (rs5498 and rs3093030) and diabetic foot (DF) susceptibility in a Chinese Han population. 128 type 2 diabetes mellitus (T2DM) patients with DF, 147 T2DM patients without DF, and 155 healthy individuals were enrolled in this study. ICAM1 polymorphisms were genotyped by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The genotypes and alleles of the polymorphisms were compared by χ 2 test between the 2 groups. Association between ICAM1 polymorphisms and DF susceptibility was expressed through odds ratio (OR) with corresponding 95% confidence interval (95%CI). Effects of ICAM1 polymorphisms on DF clinical characteristics were analyzed by t test. GG genotype of rs5498 polymorphism was distinctly correlated with decreased T2DM risk (OR = 0.369, 95%CI = 0.152–0.895) and reduced susceptibility to DF among healthy controls (OR = 0.316, 95%CI = 0.119–0.837). Similar results were discovered between rs5498 G allele and decreased risk of T2DM (OR = 0.676, 95%CI = 0.475–0.963) and DF (OR = 0.656, 95%CI = 0.453–0.950) among healthy controls. Individuals carrying rs3093030 T allele had low susceptibility to DF developed from T2DM (OR = 0.634, 95%CI = 0.412–0.974). DF patients carrying rs5498 AA genotype had significantly higher serum creatinine levels than GG genotype carriers ( P = .003). ICAM1 rs3093030 polymorphism may act as a protective factor against DF developed from T2DM, moreover, rs5498 may be involved in onset of T2DM. Clinical trial number: ChiCTR-INR-18010231. Abstract : Supplemental Digital Content is available in the text